2014
DOI: 10.1103/physreva.89.012713
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the zero-angular-momentum wave in single and double ionization of He by fast electrons

Abstract: In a recent contribution our group proposed a perturbative approach to deal with the open problem of double ionization of helium by electron impact. The goal of this work is to delve into the physics of the scattering function, and provide evidence of the nature of the single-ionization channels present in the three-body wave function. We show that the fast oscillating parts of the wave function are indeed the single-ionization channels, which appear coupled with the double continuum ones. We found a particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…However, in the high-energy regime it is possible to reduce this problem to a three-body one, by keeping the first order of a series expansion of the exact solution. In a recent work, we have shown that the three-body equivalent problem for the (e,3e) ionization can be described by the time-independent Schrödinger equation [24][25][26]:…”
mentioning
confidence: 99%
“…However, in the high-energy regime it is possible to reduce this problem to a three-body one, by keeping the first order of a series expansion of the exact solution. In a recent work, we have shown that the three-body equivalent problem for the (e,3e) ionization can be described by the time-independent Schrödinger equation [24][25][26]:…”
mentioning
confidence: 99%
“…Please see [80] (and references therein) for the role of the radial nodes for chemical bonding and the periodic table. Regarding the Coulomb-Sturmians, they are better suited for calculation of nuclear magnetic resonance shielding tensors [81] and to isolate a single atom from double ionization channels [82]. They directly involve analytical nuclear cusps and correct treatment of radial nodes.…”
Section: Resultsmentioning
confidence: 99%
“…(45)]. Once the wave function is obtained, the collisional information is extracted from it [5,30,32]. For the present kinematics, we used 50 Sturmians per coordinate.…”
Section: Wave-function Comparisonmentioning
confidence: 99%